TSH-Lowering Levothyroxine Therapy Is Associated with Higher rT3 and Stable fT3 Levels in Euthyroid Patients with Papillary Thyroid Microcarcinoma During Active Surveillance - Yoshiki Furumura; Akira Miyauchi; Mitsuru Ito; Mitsushige Nishikawa; Nozomi Yamasaki; Hideyuki Iwayama; Masumi Iwasa; Masashi Yamamoto; Makoto Fujishima; Yasuhiro Ito; Takashi Akamizu (Thyroid®, 2026)
Background: We previously reported that lowering serum thyrotropin (TSH) levels with levothyroxine (LT4) during active surveillance (AS) of papillary thyroid microcarcinoma (PTMC) was associated with a trend toward a lower rate of disease progression. In euthyroid patients with PTMC managed with mild TSH-lowering therapy, free thyroxine (fT4) levels increased, whereas free triiodothyronine (fT3) levels remained unchanged overall, thereby raising questions regarding thyroid hormone metabolism. We therefore investigated thyroid hormone balance, with particular focus on thyroxine (T4) metabolism, including serum reverse triiodothyronine (rT3). Methods: This retrospective study included patients with PTMC undergoing AS who were initially euthyroid and treated with LT4. At the final follow-up, patients were classified according to the detailed TSH score 209 in the low normal group (lower half of the reference range) and 110 in the high subnormal group (mildly subnormal range). Age- and sex-matched controls were selected from euthyroid PTMC patients undergoing AS who had not received LT4. TSH, fT4, fT3, triiodothyronine (T3), and rT3 levels were analyzed. TSH, fT4, and fT3 were measured using an electrochemiluminescence immunoassay, and T3 and rT3 were measured using liquid chromatography–tandem mass spectrometry. Results: Compared with matched controls, both the low normal and high subnormal groups showed significantly higher fT4 levels ( p < 0.001), while fT3 levels did not differ significantly. The fT3/fT4 ratio was significantly lower, whereas the rT3 levels and the rT3/T3 ratio were significantly higher in both the low normal and high subnormal groups (all p < 0.001). In analyses combining the low normal and high subnormal groups, rT3 levels were significantly and positively correlated with fT4 ( r = 0.51, p < 0.001), whereas no significant correlations were observed with TSH, fT3, or T3. Conclusions: In euthyroid patients with PTMC undergoing AS, LT4 therapy aimed at maintaining TSH within the lower half of the reference range or within the mildly subnormal range was associated with higher rT3 and stable fT3 levels. These findings raise the possibility of a compensatory buffering mechanism in thyroid hormone metabolism.